Copper-cobalt flora of Upper Katanga and Copperbelt. Field guide. Over 400 plants, 1,000 photographs and 500 drawings - Schaijes, Michel (Uliège Library, 2016)
The copper-cobalt outcrops of Upper Katanga and north-western Zambia host a particular flora which comprises an estimated 750 species of which more than 400 are treated in this copper-cobalt field guide. The aim of this book, resulting from several years of intensive field work and study, is to bring together the basic knowledges permitting an easy approach to the identification of a great number of the species to be encountered. More than 400 species are illustrated with color photographs and/or drawings together with comments concerning synonyms, habit, description, ecology and distribution. Plant species are listed and colour-coded according to classification: Cyanoprocaryota, lichenized Fungi, Anthocerophyta, Marchantiophyta and Bryophyta (red edge), Lycophyta and Monilophyta (green edge), Magnoliopsida (blue edge) and Liliopsida (yellow edge). An index allows easy location either according to genus and species. An account of the research on copper-cobalt ecosystems carried out during the last ten years in southeastern D.R. Congo is also presented. The editors have spent more than twenty years in the area concerned and have collected more than 8,500 voucher specimens, including eleven species new to science (holotypes).